2007
DOI: 10.1016/j.parkreldis.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine replacement therapy does not restore the ability of Parkinsonian patients to make rapid adjustments in motor strategies according to changing sensorimotor contexts

Abstract: The ability of dopamine replacement to restore rapid motor adjustments in Parkinson's disease was investigated. Medicated and non-medicated patients performed finger-to-nose movements while simultaneously bending the trunk forward, without vision. Trunk motion was blocked unexpectedly, necessitating rapid adjustments in arm trajectories. Patients exhibited irregular hand paths, plateaus in hand velocity, and prolonged movement times which were significantly greater in perturbed trials. Medication improved kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
4
26
2
Order By: Relevance
“…The impairment in voluntary movement in PD is characterized by a number of specific sensorimotor processing deficits, including a generalized slowness of movement; 3 a difficulty in carrying out sequential movements; 4 a reliance on sensory input, particularly visual input, to guide and correct movement; 5,6 and difficulties in timing, synchronizing, and coordinating movements. [7][8][9] Since Parkinson's disease is a degenerative disease, an effective tool is needed to track changes in its severity and the effectiveness of remedial treatments. Clinical evaluations can be costly and difficult to execute consistently over the long duration of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The impairment in voluntary movement in PD is characterized by a number of specific sensorimotor processing deficits, including a generalized slowness of movement; 3 a difficulty in carrying out sequential movements; 4 a reliance on sensory input, particularly visual input, to guide and correct movement; 5,6 and difficulties in timing, synchronizing, and coordinating movements. [7][8][9] Since Parkinson's disease is a degenerative disease, an effective tool is needed to track changes in its severity and the effectiveness of remedial treatments. Clinical evaluations can be costly and difficult to execute consistently over the long duration of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…If the BG have a critical contribution in processing sensory information for on-line movement guidance, then dysfunction in neural networks involving the BG such as in Huntington's disease (HD) and Parkinson's diseases (PD) should lead to impairments in producing effective adjustments during movement execution. However, previous studies investigating on-line movement control in BG-damaged patients have found conflicting results (Smith et al 2000;Desmurget et al 2004;Tunik et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…If the patterns of final errors are primarily determined by planning processes before the initiation of the movement, the initial kinematics of reaching movements should show similar trends and predict the pattern of final errors. Medicated and non-medicated PD patients showed a greater mean level of final 3D errors than healthy controls when proprioception was the sole source of information guiding the movement, but this difference reached significance only for medicated PD While there is considerable behavioural and neurophysiological evidence that the basal ganglia (BG) contribute to action selection and planning mechanisms, far fewer studies have examined whether these subcortical structures are involved in real-time movement guidance (Smith et al 2000;Desmurget et al 2004;Tunik et al 2007Tunik et al , 2009Roy et al 2008;Grafton and Tunik 2011). BG are part of a network that processes and integrates multisensory information to produce accurate motor action (Graziano and Gross 1993;Houk and Wise 1995;Contreras-Vidal 1999;Nagy et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The insufficiency of phasic release restoration also likely underlies the inability of Parkinson's patients on L-Dopa replacement therapy to rapidly adjust to ongoing motoric demands [108]. To accomplish a relative surge in dopamine release at a critical behavioral juncture such that the presence of dopamine provides sufficient ongoing support during more emergency situations, such as the need to escape from entrapment or predation, or falling into a body of water and needing to swim, phasic firing of nigrostriatal neurons occurs.…”
Section: Adaptation Of Endogenous Host Tissue To Neural Transplantationmentioning
confidence: 99%
“…Animal models benefit from rudimentary delivery mechanisms that also largely appear to maintain dopamine presence with little to no dynamic shifting according to "need," as might be expected of the phasic attributes of an intact dopamine system. Clearly the previously-mentioned movement tests that reveal the insufficient temporal precision of behavioral control with classic treatment has heightened awareness of the concern [108]. Nevertheless it is readily apparent that dopamine cell transplantation for the Parkinson's patient remains largely conceptualized as a more sophisticated delivery system for dopamine that may become increasingly necessary as the ongoing deterioration of dopaminergic neurons diminishes the patient's capacity to convert Levodopa into dopamine.…”
Section: Adaptation Of Transplanted Neural Cells To the Endogenous Homentioning
confidence: 99%